Nephrocalcinosis and Placental Findings in Neonatal Bartter Syndrome - Hidehiko Maruyama; Yoko Shinno; Kaori Fujiwara; Akie Nakamura; Toshihiro Tajima; Makoto Nakamura; Misao Kageyama (Thieme Medical Publishers, Inc., 2013)
Abstract Neonatal Bartter syndrome (NBS) is an inherited renal tubular disorder associated with hypokalemic alkalosis. Here we report a case of genetically diagnosed NBS. Polyhydramnios was noted at 26 weeks. A boy was born at 31 weeks and 1 day, weighed 1344 g, and had an Apgar score of 8/8. We initiated indomethacin (IND) at a dose of 0.2 mg/kg/d on day 31, and increased it to approximately 3 mg/kg/d. However, his urinary calcium (Ca) levels remained unchanged. At 4 months of age, nephrocalcinosis was detected by ultrasound. The placenta weighed 700 g (+2.7 standard deviations). Although the proportion of terminal villi was consistent with the gestational age, many of them exhibited poorly dilated capillaries. Hemosiderin pigment was seen throughout the amniochorionic connective tissue and along about 50% of the trophoblast basement membrane (TBM). Von Kossa stain revealed the corresponding area of mineralization along the TBM. In our opinion, urinary Ca levels were high and did not change after IND initiation, indicating that nephrocalcinosis may be inevitable. Enhanced inflow of maternal plasma through the basement membrane would cause Ca deposition, given that the same finding was obtained in the case with polyhydramnios. The same mechanism would also explain the hemosiderin pigment distribution.